Pengaruh Celebrity Endorser dan Sikap Pada Iklan Terhadap Sikap Pada Merek dan Loyalitas (Studi Empiris Pengguna Kartu Prabayar IM3 di Surakarta - Aji, Lintang Pamugar Mukti (Graduasi: Jurnal Bisnis & Ekonomi, 2015)
The purpose of this research  was to analyze the effect of celebrity endorser and attitude  toward  advertising  on  attitude  toward  brand  and  consumer  loyalty.This research  used  design  explanatory.  Population  were  IM3  prepaid  card  consumers  in Surakarta. The  sampling  techniquewas  convenience  sampling  with  100  respondents. Analysis used validity test, reliability test, t-test, f-test, R Square test and path analysis. The results showed that celebrity endorser significant affected on attitude toward brand.  Attitude  toward  advertising  significant  affected  on  attitude  toward  brand. Celebrity endorser significant affected on consumer loyalty. Attitude toward advertising significant  affected  on consumer  loyalty.  Attitude  toward  brand  significant  affected  on consumer  loyalty.  Celebrity  endorser  and  attitude  toward  advertising  affected  on attitude  toward  brand  simultaneous.  Celebrity  endorser,  attitude  toward  advertising and attitude toward brand affected on consumer loyalty simultaneous. The  coefficient  of  determination  of  total  results  (R2)  was  59,0%  so consumer loyalty can  be  explained  variable  celebrity  endorser,  attitude  toward  brand  within attitude  toward  brand  as  a  intervening  variables  and  the  remaining  41.0%  was explained  variables  outside  the  model.  Celebrity  endorser  is  a  proven  direct  and indirect effect on consumer loyalty. Directly affect celebrity endorser on consumer loyalty has regression coefficient is greater than regression coeficient the effect of celebrity endorser on consumer loyalty through  attitude  toward  brand.  Attitude  toward  advertising  is  a  proven  direct  and indirect effect on consumer loyalty. Directly  affect  attitude  toward  advertising  on consumer  loyalty has  regression coefficient is greater than regression coeficient regression the effect of attitude toward advertising  on consumer  loyalty through  attitude  toward  brand.  Based  on  the  result above the variable of attitude toward brand is less effective as intervening variable.